Comparison of HbA1c Levels in Patients With TB-DM And TB-non DM (Majalah Kedokteran Bandung, 2019)
Tuberculosis (TB) is still a global problem that has not currently been resolved, due to it rapid transmission through droplet nuclei released when TB patients cough, sneeze, or even talking. One of the TB comorbidities is Diabetes Mellitus (DM) that makes it necessary to do HbA1c screening in patients with TB DM and TB non-DM to prevent further disease complications.This was a cross-sectional descriptive analytic study conducted in 2018 on a total sample of 248 TB-DM and TB non-DM patients in Aceh Besar District and Banda Aceh City, Indonesia with 29.8% of the subjects were TB-DM patients and the remaining 70.2% were TB Non-DM patients. The.HbA1c levels in TB patients varied, with the average HbA1c level of 10.738 in people with TB DM and 5.426 in TB non-DM. The HbA1c level in patients with TB DM was two times higher than in TB non-DM patients. Around 21% of TB patients who were not diagnosed with DM by health care workers showed an HbA1c level that was in line with the level in the DM category. Therefore, it is recommended that each TB patient undergoes screening HbA1c in order to prevent TB non-DMpatients from becoming TB DM patients.
Keywords: HbA1c; TB; TB DM; Non-DM TB